Phylogenetic systematics of Archembiidae (Embiidina, Insecta) - Szumik, Claudia Adriana (2004)
A cladistic analysis of the American genera of Embiidae is presented, using fifty-seven representative taxa and ninety-four morphological characters. The results support the elevation (and significant re-delimitation) of the sub-family Archembiinae to family level; as delimited here, Archembiidae, revised status, includes the genera Ecuadembia n.gen., Calamoclostes Enderlein, Archembia Ross, Embolyntha Davis, Xiphosembia Ross, Ochrembia Ross, Dolonembia Ross, Conicercembia Ross, Neorhagadochir Ross, Pachylembia Ross, Rhagadochir Enderlein, Litosembia Ross, Navasiella Davis, Ambonembia Ross, Malacosembia Ross, Biguembia Szumik, Gibocercus Szumik and Pararhagadochir Davis. The results also indicate that some genera recently proposed are unjustified and therefore they are synonymized: Argocercembia Ross (a junior synonym of Embolyntha), Brachypterembia Ross (Neorhagadochir), Scelembia Ross (Rhagadochir), Ischnosembia Ross (Ambonembia) and Aphanembia Ross (Biguembia); all new synonymy. The new genus Ecuadembia is described (type species Archembia arida Ross). Ischnosembia surinamensis (Ross) is returned to the genus Pararhagadochir. The following species synonymies are established: Archembia lacombea Ross 1971=Archembia kotzbaueri (Navas 1925), Archembia peruviana Ross 2001=Archembia batesi (MacLachlan 1877), and Conicercembia septentrionalis (Mariño&Márquez1988)=Conicercembia tepicensis Ross1984; all new synonymy.The family Archembiidae, and all its constituent genera, are diagnosed and described. The genus Microembia Ross (originally described as an Embiidae) is transferred to Anisembiidae. Pachylembiinae, Scelembiinae, and Microembiinae proposed by Ross are unsupported by the present cladistic analysis.